Effect of MC3T3 cell density on osteoclastic differentiation of mouse bone marrow cells. (April 2022) - Wang, Yanhua; Li, Xiaoying; Liu, Yong; Wang, Jing; Huang, Xiaofeng
Highlights: Different cell density can affect cell proliferation and gene expression itself. With the raise of MC3T3 preosteoblast culture density, the expression of RANKL, IL-6, PGE2 and PTH also increased. Co culture of high-density MC3T3 cells and osteoclast precursors can better promoted the differentiation of osteoclasts. Abstract: Cell density has been implicated as an important property influencing cell proliferation and differentiation. Here, we investigated the impact of cell culture density on cell proliferation and osteoclastogenesis. Using various cell culture densities (1–5 × 10 4 cells/cm 2 ) of MC3T3 cells, we found that cell proliferation rates decreased as initial plating density increased over a 48-h culture period. IL-6, PGE2, and PTH expression increased as a function of increased initial plating density at the mRNA and protein levels. Similarly, RANKL expression increased with increasing initial plating density, whereas OPG changes were not significant among the groups, resulting in a decreased OPG/RANKL ratio. ELISA and Western blot showed that OPG expression was up-regulated and RANKL expression was down-regulated with increasing initial plating density, with significant difference ( p <0.05). On co-culturing primary mouse bone marrow cells with MC3T3 cells at a range of plating densities (0.5–8 × 10 4 /cm 2 ) for four days, the percentage of TRAP-positive cells increased significantly with increasing MC3T3 cell initial plating density. Therefore, MC3T3 cell proliferation rate decreased as plating density increased, while the expression of osteoclastogenesis-related genes increased. Increasing MC3T3 plating density increased the degree of primary mouse bone marrow cell osteoclast differentiation.